The Effect of Product Diversity, Display Layout And Service Quality On Consumer Satisfaction At Greensmart In Sidoarjo: Pengaruh Keragaman Produk, Display Layout Dan Kualitas Pelayanan Terhadap Kepuasan Konsumen Pada Greensmart Di Sidoarjo - Yulia Ambarsari; Lilik Indayani (Academia Open, 2021)
This study aims to determine the effect of product diversity, display layout, and service quality on consumer satisfaction at Greensmart in Sidoarjo. This research is based on the fact that there is a decline in consumers who come to Greensmart Safira Garden. The product diversity, display layout and quality of service provided are good, but according to some consumers the services provided by employees to consumers, namely hospitality and speed and responsiveness when serving at the cashier are not good. This study uses quantitative methods, data collection techniques using questionnaires, distributed to 100 respondents who have purchased products at Greensmart Safira Garden at least 2 times. The data analysis technique used in this study is multiple linear regression using the SPSS (Statistical Program for Social Science) version 18 program. The results of this study indicate that product diversity variables affect customer satisfaction, display layout variables affect customer satisfaction, service quality have an effect on consumer satisfaction, and the variables of product diversity, display layout, and service quality have a simultaneous effect on consumer satisfaction at Greensmart in Sidoarjo.